Mecanismos celulares responsáveis pela restituição da amplitude do transiente citosólico de cálcio em coração de mamífero - Antonio Nei Santana Gondim (2014)
When an extra-beat (extra-systolic contraction) is triggered in hearts cycling at a constant rate the resultant contraction is usually reduced in comparison. The amplitude of the extra-systolic contraction increases with the stimulus interval (time between normal and extra-systolic contraction), a phenomenon known as mechanical restitution. Mechanical restitution is thought to be the consequence of reduced sarcoplasmic reticulum (SR) Ca2+ release and reduction of the subsequent cytosolic Ca2+ ([Ca2+]i) transient during this restitution period. Thus, restitution (or refractoriness) of the [Ca2+]i transient is an important inherent mechanism in cardiac physiology. The aim of this study was to investigate the cellular mechanisms involved in [Ca2+]i transient restitution in mouse ventricular cardiomyocytes at physiological temperature. Simultaneous patch-clamp and confocal microscopy measurements showed that [Ca2+]i transient refractoriness was not due cardiac electrical restitution, since both action potential amplitude and L-type Ca2+ current recover much faster than the SR Ca2+ release restitution. Interestingly, measurements of [Ca2+]i transients and intra-SR Ca2+ ([Ca2+]SR) depletions revealed that [Ca2+]SR recovers to steady-state diastolic levels at a time where [Ca2+]i transient restitution is still observed. Additionally, pharmacological manipulation of the cardiac Ca2+ SR release channel (ryanodine receptors, RyR2) could significantly shift restitution curves, while minor inhibition of SR/ER Ca2+-ATPase could not. Taken together, these results suggest that the ability to subsequently activate an [Ca2+]i transient does not simply track with [Ca2+]SR refilling and also suggest the existence of time-dependent mechanism that induces a RyR2 refractory state.